(untitled) (JÓVENES EN LA CIENCIA, 2025)
The expanded instruments have gone through different variants, but electronic-digital technology has given them sufficient expansion and sound production. An expanded electric guitar is a hybrid electric-digital instrument, equipped with a joystick and foot switches. These components allow the instrument to create alternative forms of controlling 3D shapes and audio effects in real time, making a representation that goes beyond the traditional use of the guitar as a musical instrument. This instrument was developed for interacting as a MIDI controller with diverse audio and video software to generate an audiovisual experience. This tool facilitates the modification of the parameters of the visuals such as color, position, and dimensions; and it modifies them according to the sound effects you choose.